Identification of a novel CNV at the APC gene in a Chinese family with familial adenomatous polyposis - Li, Juyi; He, Chengzhi; Gong, Jing; Wang, Xiufang; Liu, Chao; Deng, Aiping; Zhu, Lin (Frontiers in Molecular Biosciences, 2023)
Introduction: Familial adenomatous polyposis (FAP) is the second most commonly inherited colorectal cancer (CRC) predisposition caused by germline mutations within the adenomatous polyposis coli (APC) gene. The molecular defects and clinical manifestations of two FAP families were analyzed, and individual prevention strategies suitable for mutation carriers in different families were proposed. Methods and results: The pathogenic gene mutations were identified among the two families using whole-exome sequencing and verified with Sanger sequencing or quantitative polymerase chain reaction (qPCR). One novel (GRCh37:Chr5: 112145676–112174368, del, 28,692 bp) and a known (c.C847T:p.R283X) mutation in the APC gene were pathogenic mutations for FAP, according to the sequencing data and tumorigenesis pattern among the family members. The two mutations led to a premature translational stop signal, synthesizing an absent or disrupted protein product. Conclusion: Our findings expand the known germline mutation spectrum of the APC gene among the Chinese population. This reaffirms the importance of genetic testing in FAP. Genetic consultation and regular follow-ups are necessary for the individualized treatment of cancer-afflicted families with APC expression deficiency. Additional work is required to develop safe and effective chemotherapy and immunotherapy for FAP based on the mutation type.